Probability theory: a complete one semester course - Dokuchaev, Nikolai (World Scientific Publishing, 2015)
This book gives a systematic, self-sufficient, and yet short presentation of the mainstream topics of an introductory Probability Theory with some selected topics from Mathematical Statistics. It is suitable for 10-14 weeks course for the second or the third year undergraduate students in Science, Mathematics, Statistics, Finance, or Economics who completed some introductory course in Calculus, including theory of integration.